Knowledge transfer program bridges gap between academia and vocational education institutions / Muhammad Hafeez Osman, Ahmad Syauqi Md Hasan and Amir Khomeiny Ruslan - Osman, Muhammad Hafeez (Unit Penerbitan FKAPP, 2022)
In a bid to strengthen the relationship between academia and vocational education institutions, Pusat Pengajian Kejuruteraan Awam (PPKA) UiTM Cawangan Pulau Pinang conducted a knowledge transfer program with three Kolej Vokasional – Perai, Taiping, and Sri Iskandar. The program was officiated by Dr Hj Anas Ibrahim, the Ketua Pusat Pengajian Kejuruteraan, and saw participation from UiTM lecturers and KV lecturers. The course included a wide range of vocational subjects, and the participants were engaged in various activities such as workshops, practical sessions, and group discussions to share their knowledge and expertise. During the course, the participants were given handouts or other materials to supplement their learning, and brainstorming sessions were conducted to generate new ideas and solutions related to the topics covered. The program kicked off with Kolej Vokasional Perai on 4/10/2022, where the participants explored the Makmal Ukur by learning to use the theodolite and closed traverse methods. The talk by Muhammad Hafeez Bin Osman and practical session with UiTM Penang's experts provided invaluable experience to the 17 students and 3 lecturers from Perai.